2012
DOI: 10.1016/j.biopsycho.2011.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Insula reactivity and connectivity to anterior cingulate cortex when processing threat in generalized social anxiety disorder

Abstract: Aberrant subcortical-prefrontal connectivity may contribute to insula hyper-reactivity to threat in generalized social anxiety disorder (gSAD). A novel PsychoPhysiological Interaction (PPI) analysis was used to examine functional ‘coupling’ between the insula and prefrontal cortex in gSAD patients and healthy controls (HCs). During fMRI, 29 gSAD and 26 HC volunteers performed an Emotional Face Matching Task, involving the processing of fear, angry, and happy expressions. As expected, compared with HCs, gSAD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
106
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(122 citation statements)
references
References 42 publications
13
106
0
3
Order By: Relevance
“…Although previous studies have demonstrated differences in activation and FC Liao et al, 2010;Prater et al, 2012;Hahn et al, 2011;Klumpp et al, 2012) between SAD and HCs, the current work is the first to use FC (and activation) to discriminate SAD vs HC diagnostic membership. The current approach of combining machine learning with large-scale, condition-dependent FC is more exploratory and data driven in identifying FC differences than previously used techniques such as PPI Analysis, which only assess FC with a single, a priori specified, 'seed' region at a time.…”
Section: Discussionmentioning
confidence: 85%
“…Although previous studies have demonstrated differences in activation and FC Liao et al, 2010;Prater et al, 2012;Hahn et al, 2011;Klumpp et al, 2012) between SAD and HCs, the current work is the first to use FC (and activation) to discriminate SAD vs HC diagnostic membership. The current approach of combining machine learning with large-scale, condition-dependent FC is more exploratory and data driven in identifying FC differences than previously used techniques such as PPI Analysis, which only assess FC with a single, a priori specified, 'seed' region at a time.…”
Section: Discussionmentioning
confidence: 85%
“…We note that, importantly, the functions of these regions are not limited to processes related to appetite and food intake regulation. These regions are also highly involved in the response to stressful stimuli in healthy controls 43 and have been implicated in anxiety disorders, including generalized anxiety disorder, 44,45 social anxiety disorder 46 and obsessive-compulsive disorder. 47,48 Although activity in the amygdala 44,46,48 and insula [45][46][47] is generally heightened in individuals with anxiety disorders (rather than hypoactive, as observed here in women with anorexia nervosa), we cannot rule out the possibility that dysfunction in these regions in women with anorexia nervosa might reflect a generalized anxiety response to food images.…”
Section: Discussionmentioning
confidence: 99%
“…However, some findings can be referred to the avoidant personality. Decreased insula-dorsal anterior cingulate functional connectivity was shown in social anxiety disorder, but not in avoidant personality disorder (Klumpp et al, 2012). Decreased connectivity between insula and ACC was confirmed when viewing negative pictures (Koenigsberg et al, 2014).…”
Section: Avoidant Personality Disorder and Its Neural Correlatesmentioning
confidence: 82%